Empowering Boja Village through Equilibrium Theory Based Gender Equality for the Enhancement of Family Welfare - Anis Widyawati; Dian Latifiani; Lyna Latifah; Rohadhatul Aisy; Shofriya Qonitatin Abidah; Siti Amatil Ulfiyah; Amel Ellsamia Indiyani; Adilia Putri Kusuma; Heru Setyanto (Universitas Negeri Semarang, 2024)
This study explores into exploring the execution of Equilibrium Theory-Based Gender Equality (ETBGE) in Boja Village to enhance family welfare, employing a non-doctrinal (empiric) approach through observation and surveys. Gender equality is crucial for holistic development, especially in rural areas, as it promotes socioeconomic progress. Drawing on Equilibrium Theory, which advocates for equal This study delves into how gender equality principles can be effectively applied at the community level to enhance access to resources and opportunities. Through systematic observation and comprehensive surveys in Boja Village, the study evaluates gender dynamics, resource allocation, decision-making processes, and overall family welfare. Analysis of empirical data, including demographic profiles, economic indicators, and social structures, aims to uncover existing disparities and challenges in achieving gender equality objectives. The findings offer insights into the effectiveness of ETBGE principles in Boja Village, identifying successful areas and those needing further intervention. The study concludes by proposing practical recommendations and strategies to empower Boja Village residents, particularly women, enabling them to participate in decision-making, access resources equitably, and enhance the welfare of their families and the community.